1996
DOI: 10.1073/pnas.93.9.4114
|View full text |Cite
|
Sign up to set email alerts
|

Centripetal cholesterol flux from extrahepatic organs to the liver is independent of the concentration of high density lipoprotein-cholesterol in plasma.

Abstract: High density lipoproteins (HDLs) play a role in two processes that include the amelioration of atheroma formation and the centripetal flow of cholesterol from the extrahepatic organs to the liver. This study tests the hypothesis that the flow of sterol from the peripheral organs to the liver is dependent upon circulating HDL concentrations. Transgenic C57BL/6 mice were used that expressed variable amounts of simian cholesteryl ester-transfer protein (CETP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 44 publications
3
52
1
Order By: Relevance
“…According to our results, ABCA1 does not significantly control total body cholesterol fluxes, even under highly stressed conditions. Assuming that the overall centripetal cholesterol flux in the mice used in these studies is of the same order of magnitude as that reported in several other mouse models (51,52,56), our results strongly suggest that ABCA1 is not involved in control of this flux. Since very low HDL levels resulting from the absence of apoA-I also do not influence centripetal cholesterol flux in mice (56-58), we hypothesize that HDL does not play a quantitatively important role in this pathway of cholesterol transport.…”
Section: Figuresupporting
confidence: 54%
See 1 more Smart Citation
“…According to our results, ABCA1 does not significantly control total body cholesterol fluxes, even under highly stressed conditions. Assuming that the overall centripetal cholesterol flux in the mice used in these studies is of the same order of magnitude as that reported in several other mouse models (51,52,56), our results strongly suggest that ABCA1 is not involved in control of this flux. Since very low HDL levels resulting from the absence of apoA-I also do not influence centripetal cholesterol flux in mice (56-58), we hypothesize that HDL does not play a quantitatively important role in this pathway of cholesterol transport.…”
Section: Figuresupporting
confidence: 54%
“…Elucidation of the factors involved in regulation of this HDL-mediated pathway is therefore of prime importance. Detailed information about the magnitude of the different cholesterol fluxes in the bodies of rodents has been generated in a series of elegant studies from Dietschy's group (2,(47)(48)(49)(50)(51)(52)(53). An important conclusion from their work is that reverse cholesterol transport, which they call "centripetal cholesterol flux," is not determined by the plasma level of HDL, but by processes in peripheral tissues that make cholesterol available for uptake by nascent HDL particles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in transgenic mice have shown that arterial macrophages contribute little to HDL-cholesterol (8 ) and that the plasma HDL-cholesterol concentration is not a reliable indicator of the rate of flux of cholesterol from peripheral tissues to the liver (9,10 ). Plasma HDL-cholesterol is influenced by the lipolysis of TGRLs, by the transfer of CEs to apo B-containing lipoproteins via CETP (7 ), and by the activity of the ABCA1 transporter in liver cells (19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This challenges and dampens the traditional notion of reverse cholesterol transport from peripheral cells to the liver via HDL (84) The knowledge of the sites and control of ABCA1 expression has already prompted the discussion of the concept of reverse cholesterol transport (16). Intriguingly, the HDL level appears to have no relation to net flux of cholesterol through HDL (85).…”
Section: Effect Of Abca1 Deficiency On Distribution Of Hapoa-i and Chmentioning
confidence: 99%